The perception of students towards forum subject at the Faculty of Music, Uitm / Nadira Zulkifli. - Zulkifli, Nadira (2011)
The purpose of this study was to investigate the perception of students' towards Forum subject and perception of failure towards Forum at the Faculty of Music in UiTM Shah Alam. The respondents of this study were 122 comprising 56 males and 66 females. Questionnaires were distributed randomly to three music programs which are Diploma in Music, Bachelor in Education and Bachelor in Performance. Finding shows that a majority of respondents from all programs have high self-efficacy and strongly agree with the Forum subject. There are correlations between the students' perception towards Forum and students' perception of failures towards factors of failure towards Forum among music students.